Rabies and the pandemic: lessons for One Health. (14th August 2021) - Nadal, Deborah; Beeching, Sarah; Cleaveland, Sarah; Cronin, Katy; Hampson, Katie; Steenson, Rachel; Abela-Ridder, Bernadette
Abstract: This article examines the impact of coronavirus disease 2019 (COVID-19) on dog-mediated rabies, a neglected tropical disease that remains endemic in >65 countries. A globally agreed strategy for rabies elimination is underpinned by a One Health approach, coordinating human and animal health sectors and engaging communities. We present data on the scale and nature of COVID-19 disruption to rabies control programmes and the wider learning for One Health implementation. We argue that the global shift in health priorities caused by the pandemic, and consequent side-lining of animal health, will have broader ramifications for One Health implementation and preparedness for future emergent zoonoses.